An Analysis of the Photo-Thermoelastic Waves Due to the Interaction between Electrons and Holes in Semiconductor Materials under Laser Pulses - Hashim M. Alshehri; Khaled Lotfy (Mathematics, 2022)
In this paper, the interaction between holes and electrons in semiconductor media is analyzed based on the existing mathematical–physical model. The elasto-thermodiffusion (ETD) theory, according to photothermal (PT) transport processes, has been used to study the model under the impact of the non-Gaussian laser pulse. A one-dimensional (1D) electronic/thermoelastic deformation is described, in detail, by the governing field equations. The governing field equations are taken in non-dimensional forms. The governing equations are established based on coupled elasticity theory, plasma diffusion equations, and moving equations. To determine the physical field quantities in this problem analytically in the Laplace domain, some boundary conditions are taken at the free surface of the semiconductor medium. The inversion of the Laplace transform is implemented using a numerical method to obtain the complete solutions in the time domain for the basic physical fields involved. The effects of the phase lag (relaxation time) of the temperature gradient, phase lag of the heat flux, and laser pulses are graphically obtained and discussed in comparison to silicon and germanium semiconductor materials. The wave behavior of the main fields in the semiconductors, according to optoelectronics and the thermoelastic processes, is obtained and graphically represented.